PENERAPAN MODEL DISCOVERY LEARNING DENGAN MEDIA DIORAMA PAPERCRAFT DALAM PEMBELAJARAN MENULIS TEKS DESKRIPSI PADA PESERTA DIDIK KELAS VII MTs DARUL FALAH BONGAS TAHUN PELAJARAN 2024/2025 - Amelia, Dhea; Ahmad Maskur Subaweh; Muhammad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning to write descriptive texts faces several problems, including students' difficulty in expressing ideas, low interest and enthusiasm, poor language use, monotonous learning, and a lack of active interaction between teachers and students. The discovery learning model and papercraft diorama media can be alternatives to improve students' descriptive writing skills. The objectives of this study are: 1) to test the effectiveness of the discovery learning model and papercraft diorama media in teaching descriptive text writing to seventh-grade students at MTs Darul Falah Bongas for the 2024/ 2025, and 2) to determine how students engage in descriptive text writing instruction by applying the discovery learning model and papercraft diorama media among seventh-grade students at MTs Darul Falah Bongas for the 2024/2025 academic year. This study employs an experimental method with a nonequivalent control group design. Based on statistical calculations using the independent samples t-test, the calculated t-value was 3.347 and the table t-value was 2.000. Thus, the calculated t-value (3.347) > table t-value (2.000), indicating that H1 is accepted and H0 is rejected. Thus, it can be stated that the discovery learning model and diorama papercraft media are effective when applied in teaching descriptive text writing to seventh-grade students at MTs Darul Falah Bongas in the 2024/2025 academic year. Based on the analysis of the observation data results.